Peran Keluarga Terutama Ibu sebagai Madrasah Pertama dalam Pendidikan Keluarga - Nurcahyaningtias, Novia Dwi; Julaeha, Siti (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
Family education is a very important education, especially Islamic education, where this education must be introduced early. It also functions as a basic foundation for the formation of the child's personality, in this case the role of parents as the first and main educator is needed, especially the mother. The slogan “mother is the first madrasa” represents how mother is the first figure of direct influence, who not only teaches the basic values of life, but also prepares children to understand various social, moral and emotional dimensions. This research aims to explore how mothers, as the first madrasa, provide education to children in the family context, both in the aspects of character building, attitudes, and behaviour. This study uses a qualitative approach with in-depth interviews with mothers from various socio-economic backgrounds, as well as observations of mother-child interactions at home. The results showed that mothers play an important role in teaching values such as compassion, discipline, empathy, and social skills that form the basis of children's character development. Mothers who actively provide education based on good examples and communication tend to produce children who are more independent, confident and have a positive attitude towards life. The study also found that although the role of mothers is dominant, the contribution of fathers and other family members also influences the success of education in the family. Thus, this study confirms the importance of the mother's role as the first madrasa in children's education, and provides recommendations to strengthen support for mothers in this educational role through programmes that support the dual role of mothers as caregivers and educators.